AKSEBILITAS KONSUMEN TERHADAP BERBAGAI BAHAN BAKSO - Uci Sukarno Putri; Agustina Widyasworo; Ahmad Rofiq Ghozali (Universitas Islam Balitar, 2018)
Seeing the need for beef animal foods that continue to increase, but beef on the market does not meet the market's needs, experts have the initiative to meat. Animal meat in this study was beef, chicken, duck and rabbit. One of the processed meat products that has long been known and very popular with Indonesian people is meatballs. This research is used for various types of meatball ingredients. The level of consumer acceptance used in this study uses organoleptic tests through sensory devices. Penel that in this study is a consumer panel consisting of 30 investigators. Palatability of panelists can be done through an organoleptic test which includes taste, color, aroma, texture and elasticity by waiting for RAL statistical tests. The results of acceptability study showed that the respondent's response to beef meatballs was not higher / better than recurrent meatballs (chicken, duck, rabbit).